Technological frames in classroom: a case study for a faculty professional development - Merve Basdogan; Tracey Birdwell; Tripp Harris (Association for Learning Technology, 2022)
Introducing new technologies to faculty members provides opportunities to reconstruct the ways they teach, evaluate, interact, and communicate. Yet, the personal and organisational perceptions regarding the nature of technology can filter, frame, and guide faculty's interactions with technology. In this case study conducted in a faculty professional development context, we carried out a thematic analysis to explore the technological interpretations in the faculty's definitions of technology. We analysed 32 definitions through Mitcham's technological frames categories, and it was observed that faculty attached various meanings to technology in terms of (1) object, (2) knowledge, (3) activity, and (4) volition perspectives. The role of self-interactions and social interactions in higher education has been discussed regarding the formation of technological understanding.